2020
DOI: 10.3389/fchem.2020.587474
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Bridged Synthesis of Ternary h-BN@PDA@TiO2 as Nanoenhancers for Thermal Conductivity and Flame Retardant of Polyvinyl Alcohol

Abstract: In this study, h-BN@PDA@TiO 2 hybrid nanoparticles were prepared and used as functional fillers to prepare PVA nanocomposites, and the effects of hybrid particles on PVA thermal conductivity and flame retardant properties were studied. The results showed that hybrid particles could significantly improve the thermal conductivity and flame retardant performance of PVA composites, and effectively inhibit the release of toxic gases such as combustible pyrolysis products and CO, which enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…4b). 42 And the percentage of N–H bond increases greatly from 9.1% for pristine h-BN to 23.1% for h-BN@CDs, which may be attributed to the formation of hydrogen bonding between the CDs and N atoms of h-BN. The C 1s spectra can be divided into three peaks located at 284.6, 285.8 and 288.7 eV, which are allocated to the C–C, C–OH, and CO species, respectively (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…4b). 42 And the percentage of N–H bond increases greatly from 9.1% for pristine h-BN to 23.1% for h-BN@CDs, which may be attributed to the formation of hydrogen bonding between the CDs and N atoms of h-BN. The C 1s spectra can be divided into three peaks located at 284.6, 285.8 and 288.7 eV, which are allocated to the C–C, C–OH, and CO species, respectively (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Introducing highly conductive composites into wood was a common method for promotion of TC. 8,16,17,26,27 Figure 3C and Table 1 listed the comparison of the TC of wood polymer composites in the open. Clearly the TC value of wood composites reinforced with polymer composites such as polyamideimide (PAI), A(FCN), MWCNTs, Boron nitride (BNNS), and As 2 O 3 were between 0.28 and 0.71 Wm À1 K À1 , which were difficult to further reserve the original structure of wood and excessive amount of inorganic fillers.…”
Section: Thermal Stability Of Monterey Pine/mep Compositesmentioning
confidence: 99%
“…This series includes eight research articles that cover a wide range of flame retardant polymer materials, including epoxy resin (Kong et al, 2020;Yi et al, 2020), polypropylene (Liu et al, 2020), polystyrene (Shi et al, 2020), polyurethane (Hu et al, 2021), polyvinyl alcohol (Wang et al, 2020) and flame retardants based fire-fighting foams (Li et al, 2021a;Li et al, 2021b Yi et al (2020) presented a Spiro-phosphorus (P)-based reactive flame-retardant epoxy resin curing agent. The synthesized epoxy thermosets exhibit higher carbon residue yield with significant improvements to flame retardancy and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ADP and EG on the structure, thermal conductivity, thermal stability, and flame retardant performance of RPUF was investigated. Wang et al (2020) studied ternary h-BN@PDA@TiO2 hybrid nanoparticle as functional fillers for PVA nanocomposites. The results showed that the hybrid particles could significantly improve the thermal conductivity and flame retardant performance of the PVA composites and effectively inhibit toxic gases emissions such as combustible pyrolysis products and CO. Li et al (2021a) presented the preparation and fire suppression performance of mixing nano magnesium hydroxide particles and water-soluble flame retardant 8124 as an aqueous film forming fire extinguishing agent (AFFF).…”
Section: Introductionmentioning
confidence: 99%